Broca's aphemia: an illustrated account of its clinico-anatomic validity - Ricardo de Oliveira‐Souza; Jorge Moll; Egas Caparelli-Dáquer (2007)
OBJECTIVE: To present the case of a 54-year-old man with loss of speech, but with preservation of voluntary facio-lingual motility, language and other cognitive abilities (Broca's aphemia). METHOD: Observation of patient oral communicative abilities and general behavior, neuropsychological assessment and cranial computed tomography. RESULTS: Computed tomography showed a hyperdense lesion in the subcortex of the left precentral gyrus corresponding to Brodmann's area 6 and 44. Neuropsychological assessment confirmed that the major cognitive domains were intact. CONCLUSION: Our patient reiterates the validity of Broca's aphemia as a clinico-anatomic entity allowing us to portray it for the first time in pictures. From a neurobehavioral perspective, aphemia is related to apraxia rather than to aphasia, a fact that may have hampered the full grasp of its far-reaching implications for neurology and aphasiology.